Foundations of inorganic chemistry - Winter, Mark J.; Andrew, John E. ([S.l.] : Oxford University Press, 2001)
Intended to complement Foundations of Organic Chemistry , the best-selling Primer by Michael Hornby and Josephine Peach, this text is a broad overview of inorganic chemistry. Writing in an informal and relaxed style, Mark Winter and John Andrew cover the basics and also highlight the industrial and environmental relevance of inorganic chemistry.